2019
DOI: 10.1101/644682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

β-bursts reveal the trial-to-trial dynamics of movement initiation and cancellation

Abstract: The neurophysiological basis of motor processes and their control is of tremendous interest to basic researchers and clinicians alike. Notably, both movement initiation and cancellation are accompanied by prominent field potential changes in the β-frequency band . In trial-averages, movement initiation is indexed by β-band desynchronization over sensorimotor sites, while movement cancellation is signified by β-power increases over (pre)frontal areas. However, averaging misrepresents the true nature of the β-si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(100 citation statements)
references
References 70 publications
9
90
1
Order By: Relevance
“…The changes in the accumulated duration of beta bursts induced by neurofeedback training positively correlated with the shortening of reaction time. These results are consistent with previous studies which demonstrated a positive correlation between beta bursts and reaction time (Little et al, 2019;Wessel 2019), but as we purposefully modulated beta bursting through neurofeedback we also provide evidence in favour of a causal link between transient beta bursts and motor function.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The changes in the accumulated duration of beta bursts induced by neurofeedback training positively correlated with the shortening of reaction time. These results are consistent with previous studies which demonstrated a positive correlation between beta bursts and reaction time (Little et al, 2019;Wessel 2019), but as we purposefully modulated beta bursting through neurofeedback we also provide evidence in favour of a causal link between transient beta bursts and motor function.…”
Section: Discussionsupporting
confidence: 92%
“…The timing of beta bursts in the motor cortex prior to movement was related to the duration of motor preparation, with later bursts resulting in delayed response times (Little et al, 2019). Wessel (2019) also found that an increased rate of beta bursts in the contralateral sensorimotor cortex following a Go cue predicted a longer reaction time. However, all these studies are correlational, and it is still not clear whether modulating sensorimotor beta bursts can lead to changes in motor preparation and movement initiation.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies suggest that event-related desynchronizations and synchronizations, such as PMBR, are driven by beta bursts (Little et al, 2019 ; Seedat et al, 2020 ; Wessel, 2020 ) which carry more information than the trial-averaged band oscillation. At the same time, a recent study suggested spatial differences between beta oscillations that reflect implicit and explicit learning (Jahani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We now measured scalp EEG as well as EMG from the hand, in 11 participants (see Table 1 for behavioral results). We derived beta bursts rather than beta power per se, as bursts have richer features (Shin et al, 2017) [also see (Little et al, 2018;Wessel, 2019a)], such as burst timing and duration. To identify right frontal electrodes of interest in each participant (i.e.…”
Section: B C Dmentioning
confidence: 99%